Clinical Outcomes of Pregnant and Postpartum Extracorporeal Membrane Oxygenation Patients. (19th November 2020) - Lankford, Allison S.; Chow, Jonathan H.; Jackson, Amanda M.; Wallis, Marianne; Galvagno, Samuel M.; Malinow, Andrew M.; Turan, Ozhan M.; Menaker, Jay A.; Crimmins, Sarah D.; Rector, Raymond; Kaczorowski, David; Griffith, Bartley; et al.
Abstract : BACKGROUND: The use of extracorporeal membrane oxygenation (ECMO) as a rescue therapy for cardiopulmonary failure is expanding in critical care medicine. In this case series, we describe the clinical outcomes of 21 consecutive pregnant or postpartum patients that required venovenous (VV) or venoarterial (VA) ECMO. Our objective was to characterize maternal and fetal survival in peripartum ECMO and better understand ECMO-related complications that occur in this unique patient population. METHODS: Between January 2009 and June 2019, all pregnant and postpartum patients treated with ECMO for respiratory or circulatory failure at a single quaternary referral center were identified. For all patients, indications for ECMO, maternal and neonatal outcomes, details of ECMO support, and anticoagulation and bleeding complications were collected. RESULTS: Twenty-one obstetric patients were treated with ECMO over 10 years. Thirteen patients were treated with VV ECMO and 8 patients were treated with VA ECMO. Six patients were pregnant at the time of cannulation and 3 patients delivered while on ECMO; all 6 maternal and infant dyads survived to hospital discharge. The median gestational age at cannulation was 28 weeks (interquartile range [IQR], 24–31). In the postpartum cohort, ECMO initiation ranged from immediately after delivery up to 46 days postpartum. Fifteen women survived (72%). Major bleeding complications requiring surgical intervention were observed in 7 patients (33.3%). Two patients on VV ECMO required bilateral orthotopic lung transplantation and 1 patient on VA ECMO required orthotopic heart transplantation to wean from ECMO. CONCLUSIONS: Survival for mother and neonate are excellent with peripartum ECMO in a high-volume ECMO center. Neonatal and maternal survival was 100% when ECMO was used in the late second or early third trimester. Based on these results, ECMO remains an important treatment option for peripartum patients with cardiopulmonary failure.